Neck circumference as a discriminator of obesity in older women enrolled in a physical activity program Perímetro do pescoço: Discriminador de obesidade em idosas praticantes de atividade física - Petreca D.R. (2017)
© 2017, Universidade Federal de Santa Catarina. All rights reserved.The aim of this study was to evaluate neck circumference (NC) as a discriminator of overweight and obesity and to establish cut-off points for physically active older women. The sample consisted of 170 older women (69.5 ± 6.8 years) practicing physical activity. Anthropometric measures (body weight, height, waist circumference – WC, and NC) were obtained and the body mass index (BMI) was calculated. Correlation analysis was performed and ROC curves were constructed. NC was significantly correlated with BMI (rho = 0.656; p<0.0001) and WC (r = 0.561; p<0.0001). Correlating BMI with NC, areas under the ROC curve of 0.819 (p=0.0001) for overweight and of 0.902 (p=0.0001) for obesity were obtained, with suggested cut-off points of 33.07 and 34.05 cm, respectively. Correlating WC with NC, areas under the ROC curve of 0.711 (p=0.0014) for moderate risk (WC) and of 0.864 (p=0.0001) for high risk were obtained, with suggested cut-off points of 32.15 and 34.15 cm, respectively. NC was associated with BMI and WC. An NC ≥ 34 cm was a risk factor for obesity and abnormal body fat distribution in the older women studied. This anthropometric parameter is an alternative to discriminate overweight and obesity in physically active older women.